Sustainability of coffee land use upon conversion from natural forest in Western Ghats of South India: An evaluation. (7th February 2021) - Karthika, Kavukattu Sreekumar; Anil Kumar, Kokkuvayil Sankaranarayanan; Nair, Krishna Pillai Madhusoodanan; D'Souza, Violet M.; Nagaraja, Jambaradi Satyanarayana; Lalitha, Manickam; Koyal, Arti; Jayaramaiah, Maheswarappa; Parvathy, Sreekumar; Sujatha, Karumathil; Shivanand, Khandal; Ramamurthy, Venkataramanappa; et al.
Abstract: The variability of soil qualities across the coffee‐growing areas and consequences of conversion of forest to coffee plantations on soil qualities and sustainability in the Western Ghats of South India are evaluated in this study by assessing and studying the six representative pedons selected from Chikmagalur district in Karnataka and Wayanad and Idukki districts of Kerala taking into consideration of the agro‐ecological zones, they belong. Sixty sites were located for monitoring soil quality, of which 46 sites were located in coffee plantations of all agro‐climates and 14 in forests adjacent to coffee plantations in similar setting. Soil quality indicators were selected by carrying out principal component analysis (PCA) on measured soil attributes, which provided 4 PCs in both land uses with eigen values > 1 and explaining at least 5 per cent variance in data set. The indicators for coffee land use were pH, exch. Al and CEC and for forest land use, organic carbon, pH and exch. Al. These indicators were transformed into scores following linear scoring method and soil quality index was determined, on a scale of 0–1, using the weighting factors obtained from PCA. Soil quality index was high (0.836) for natural forest land use, while it was medium (0.634) for coffee land use. Results indicated that organic carbon, pH and exch. Al are the most powerful indicators of soil quality. Proper management of soil acidity in coffee plantations due to liming, pooling back of nutrients, fertilization effect and other anthropogenic interventions in them have helped in maintaining a near equal soil quality to that of natural forest, which can be made sustainable by adopting effective plantation management practices.